Sonar mining of deeply located foreign bodies in the musculoskeletal system - Çaçan, Mehmet Akif; Birinci, Murat; Uzel, Kadir; Yılmaz, Mehmet Kürşat; Kemah, Bahattin; Tuğrul, Ali İhsan (My University, 2024)
Introduction: Foreign body (FB) injuries constitute an important part of admission to emergency and orthopedic clinics in daily practice. The localization and removal of FBs can be difficult. Ultrasound (USG) plays an important role in the localization of FBs. In this study, we aimed to present the results of patients who underwent US-guided FB extraction. Methods: Fifty-seven patients who were admitted to the emergency service and orthopedic outpatient clinic due to FB trauma to soft tissue were retrospectively evaluated. USG-guided removal was performed under local anesthesia. The number, size, shape, structure, distance to the skin, and integrity of the FB were determined using USG guidance. Patient satisfaction was evaluated with Results: The mean duration of surgery was 7 min (range; 5 to 20 minutes), and the mean incision size was 11 mm (range; 5 to 25 mm). Forty-seven of the patients underwent an outpatient procedure and were discharged on the same day. No postoperative complications were observed. Fifty one of 57 (89.5%) were very satisfied with the surgery. Conclusion: Consequently, USG-guided FB extraction is a safe, fast, and comfortable option for the patient and the physician. Orthopedic physicians should receive USG training starting from their assistantship, and its use in daily practice should be increased.
Keywords: Ultrasound; Soft Tissue; Foreign Body